If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11y + -6x = 0 Reorder the terms: 3x + -6x + -11y = 0 Combine like terms: 3x + -6x = -3x -3x + -11y = 0 Solving -3x + -11y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11y' to each side of the equation. -3x + -11y + 11y = 0 + 11y Combine like terms: -11y + 11y = 0 -3x + 0 = 0 + 11y -3x = 0 + 11y Remove the zero: -3x = 11y Divide each side by '-3'. x = -3.666666667y Simplifying x = -3.666666667y
| 3(x-2)=-26-7x | | 7z-1=2(4z-3) | | (x+64)=(2x+39) | | 40+5x=5(7+2x) | | 3/4x-9=7 | | (3/2)x-163x | | -23=-9f-4f | | 2x+4y+2-y-9x-5= | | 4.75t+5=13.5t+12 | | Y=cos(5*x)+sin(5*x) | | 3m-4n-7=8m+n-6 | | 24-8x=-2(4x+10) | | 3y+-5=5y | | 90+(3x-1)+31=180 | | 4.19/4 | | 7(5x-3)=10 | | 2x(100/45):3x(100/36) | | 9h-3-6h=16 | | 2(3x+6)+3(3x-4)= | | 0.06/1=x/30 | | 3z-4z=-30 | | 2+5=x-7 | | 4x-5(6x-6)=2-7(x-5) | | 1.14/1=x/30 | | 8-z=-22 | | 16/54 | | 4v-7v=-21 | | -20=7+9x | | 0.06/1=x/5 | | -7x+7=-5x+25 | | 0=4x^2+2x+32 | | K/-8.8=-12.9 |